Competências definidas nas diretrizes curriculares nacionais do curso de graduação em administração : suas traduções para os planos de ensino - Arantes, Sandra Stöckli (2017)
The professionals that work in the teaching of the Administration coexist with a great challenge expressed by the demands of the eight great competences and abilities foreseen in the National Curricular Guidelines (DCN) of the Bachelor's Degree in Administration. These competencies are expected to be achieved by the way they are presented in the Teaching Plans (PE) when contemplating theory and practice, through content based on syllabi, bibliographies and methodologies. The main research focus is the fact of knowing if the scope occurs the manner how the translations are presented in the lesson plans, through the Teaching Plans (PE), by the curricular units Professors. Therefore, in this study the translations in Derrida are taken in movements with the purpose of analyzing how the Professors translate what is already described regarding the skills and abilities expected in the alumnus‟profile, members of the Pedagogical Project of Course (PPC), extracted from the Curricular Guidelines (DCN) for Teaching Plans (PE). In such context, the research problem arises which wonders if, indeed, these translations, through the Education Plans (PE), manage to provide a training for the graduates that reveals the competences foreseen in the Guidelines. The general objective is to understand if the competences defined in the Guidelines, contemplated in the Pedagogical Project of the Course (PPC) and formulated in the Teaching Plans (PE), of the curricular component, can be evaluated and certified in fact so that, at the end of the course, after four years the administrator professional training is reached. The problem defined, in spite of the practice adopted by the course emphasizing competences, was not fully answered, and therefore it is not possible to understand if the evaluations are successful and, consequently, they translations the defined competences, within the scope of the National Curricular Guidelines (DCN), Members of the aluminus profile.